2021
DOI: 10.5014/ajot.2021.043562
|View full text |Cite
|
Sign up to set email alerts
|

Evidence to Inform Occupational Therapy Intervention With Adults With Intellectual Disability: A Scoping Review

Abstract: were published in a peer-reviewed journal, (3) included content about people ages 18 yr or older with primary or coexisting ID at any level, and (4) included information relevant to occupational therapy practice (e.g., related to occupational performance strengths and needs of people with ID). Articles were excluded if they (1) were literary criticism (e.g., book reviews, editorials) or conference proceedings; (2) were gray literature (e.g., dissertations, government reports); or (3) included only participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…As well as addressing the accessibility of the physical environment, there are opportunities for occupational therapists to support adults aging with ID in other domains of life (Blaskowitz et al, 2021). Descriptive statistics in this study showed many people aging with ID don't have friends outside of their home, and require support for ADL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As well as addressing the accessibility of the physical environment, there are opportunities for occupational therapists to support adults aging with ID in other domains of life (Blaskowitz et al, 2021). Descriptive statistics in this study showed many people aging with ID don't have friends outside of their home, and require support for ADL.…”
Section: Discussionmentioning
confidence: 99%
“…This could include working at an individual level with adults aging with ID and their support staff to analyze activities and occupations that best match their abilities and interests, and providing specialized advice to support their participation in meaningful work and leisure activities. Occupational therapists can play a significant role in advocating for and implementing occupation-focused approaches that enable adults with ID to continue to participate in meaningful work and leisure opportunities as they grow older (Blaskowitz et al, 2021; Johnson et al, 2019). Occupational therapists can work directly with adults aging with ID, or through consultative or coaching approaches with support staff or family members to facilitate participation in work or leisure occupations (Johnson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors followed scoping review procedures as outlined by Arksey and O'Malley (2005) and determined the research question for the larger scoping review to be: What is the scope of the evidence related to OT practice with adults with ID? Keywords and controlled vocabulary terms (e.g., "cognitive impairment," "intellectual disability," "mental retardation," "occupational therapy") were developed by a consulting librarian and custom searchers were completed in PubMed, CINAHL, PsycINFO, and Scopus (Blaskowitz et al, 2021;Mahoney et al, 2021). Citations and abstracts from the searches were maintained in Covidence (Veritas Health Innovation, 2019), a web-based review management system.…”
Section: Scoping Review Proceduresmentioning
confidence: 99%